1985
DOI: 10.1093/cvr/19.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aspirin and indomethacin on exercise-induced changes in blood pressure and limb blood flow in normal volunteers

Abstract: To evaluate the possible role of prostaglandins in exercise-induced changes in blood pressure and limb blood flow we have compared the effects of aspirin and indomethacin in a double-blind placebo controlled study in a group of normal volunteers. Nine men undertook treadmill exercise after pretreatment with placebo, aspirin and indomethacin. Indomethacin caused a greater increase in systolic blood pressure during exercise than aspirin (p less than 0.05) and a smaller fall in diastolic pressure than either plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…This is consistent with the findings of other studies in which a COX inhibitor (aspirin, indomethacin, or ibuprofen) was given systemically (4,21,34). By contrast, when indomethacin or aspirin was directly infused into the forearm circulation, baseline FVC decreased and venous efflux of PGI 2 and PGE 2 decreased, indicating a tonic dilator influence of PGs (6,38).…”
Section: Effects Of Aspirinsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the findings of other studies in which a COX inhibitor (aspirin, indomethacin, or ibuprofen) was given systemically (4,21,34). By contrast, when indomethacin or aspirin was directly infused into the forearm circulation, baseline FVC decreased and venous efflux of PGI 2 and PGE 2 decreased, indicating a tonic dilator influence of PGs (6,38).…”
Section: Effects Of Aspirinsupporting
confidence: 90%
“…More recently, both indomethacin and aspirin substantially reduced the increase in calf blood flow and decrease in vascular resistance that occurred following a 30-min period of treadmill exercise (4). In this study, a placebo or one of the COX inhibitors was given on different experimental days in randomized order.…”
mentioning
confidence: 98%
“…We have confirmed that vasodilatory prostanoids are important in determining the response to ACh in both diabetic (4) and nondiabetic subjects (11,12). We have also demonstrated that, in the absence of pretreatment with a cyclo-oxygenase inhibitor, endothelium-dependent vasodilation is not impaired in type 1 diabetic patients who have no evidence of additional macrovascular risk.…”
Section: Prostaglandin-mediated Vasodilation In Type 1 Diabetessupporting
confidence: 70%
“…There is evidence that vasodilatory prostanoids may be important in determining responses to ACh in both diabetic (4) and nondiabetic subjects (11,12), their effects being mediated through an increase in cyclic AMP. We hypothesized that increased prostaglandin-mediated vasodilation might compensate for decreased activity of the NO pathway in type 1 diabetes.…”
mentioning
confidence: 99%
“…3233 Although Stassen et al 33 found no increase in systemic vascular resistance after treatment with indomethacin, Cowley et al 32 found that calf blood flow measured immediately postexercise was attenuated by about 40%. However, oral administration of indomethacin may have minimized the drug's effectiveness, since intravenous injection of indomethacin has been shown to augment vascular resistance in dynamically contracting dog skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%